YASH Scoring System for the Diagnosis of Acute Appendicitis - Kumar, Rohit; Shafiq, Mahrukh; Ali, Aun; Iqbal, Muhammad Mansoor; Jabeen, Sana; Bilal, Roha (Biological and Clinical Sciences Research Journal, 2025)
Acute appendicitis is one of the most frequent surgical emergencies worldwide. Early and accurate diagnosis is crucial to prevent complications such as perforation or unnecessary surgeries. Clinical scoring systems, such as the YASH score, have been developed to aid in diagnosis; however, their accuracy requires validation in different populations. Objective: To evaluate the diagnostic accuracy of the YASH scoring system in predicting acute appendicitis by assessing its sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Methods: A prospective observational study was conducted at Fazaia Ruth Pfau Medical College, PAF Hospital, Faisal, Karachi, from August 1, 2023, to July 1, 2024. Ethical approval was obtained from the institutional review board. A total of 100 patients aged 10 years and above of both genders presenting with suspected acute appendicitis (symptoms including right lower quadrant pain, fever, nausea, vomiting, and tenderness on examination) were enrolled using a non-probability consecutive sampling technique. Diagnostic performance of the YASH score was evaluated against surgical and histopathological outcomes. Sensitivity, specificity, PPV, NPV, and area under the ROC curve (AUC) were calculated using standard statistical methods. Results: The YASH scoring system showed a sensitivity of 89.04%, indicating high accuracy in identifying true appendicitis cases. The specificity was 85.19%, signifying good ability to exclude non-appendicitis cases. The PPV and NPV were consistent with the diagnostic trend. ROC curve analysis yielded an AUC value of 0.912, confirming strong overall performance in predicting acute appendicitis. Conclusion: The YASH scoring system demonstrated high diagnostic accuracy in predicting acute appendicitis with excellent sensitivity, specificity, and AUC. It can be reliably utilized as a clinical decision-making tool, especially in resource-limited settings where imaging may not be readily available.